2017
DOI: 10.3390/ma11010022
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation Mechanism of a Thermostable Polyester Stabilized with an Open-Cage Oligomeric Silsesquioxane

Abstract: A polyester composite was prepared through the polymerization of an unsaturated ester resin with styrene and an open-cage oligomeric silsesquioxane with methacrylate groups. The effect of the open-cage oligomeric silsesquioxane on the thermal stability of the thermostable polyester was studied using both thermogravimetric analysis and differential thermal analysis. The results showed that the methacryl oligomeric silsesquioxane improved the thermal stability of the polyester. The decomposition mechanism of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The HO-POSS, oppositely to amine-POSS and Gly-POSS, is an open-cage polyhedral oligomeric silsesquioxane. Bautista Y. et al [ 59 ] showed the slight positive impact of open-cage oligomeric silsesquioxanes on the thermal stability of polyester due to the shift of the temperature at 50% weight loss. Here, also, a slight shift of T 50% for all PCL POSS compositions from 421 to 424 °C was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The HO-POSS, oppositely to amine-POSS and Gly-POSS, is an open-cage polyhedral oligomeric silsesquioxane. Bautista Y. et al [ 59 ] showed the slight positive impact of open-cage oligomeric silsesquioxanes on the thermal stability of polyester due to the shift of the temperature at 50% weight loss. Here, also, a slight shift of T 50% for all PCL POSS compositions from 421 to 424 °C was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Badia et al developed waterborne PSA formulations with 72% of biocontent through emulsion polymerization of commercial biobased monomers octyl acrylate and isosorbide methacrylate and achieved much higher peel strength (8.9 N/25 mm) and tackiness of 8.3 N . Our group has also previously developed UV curable PSAs derived from cardanol-based PU acrylates and lignin acrylates with acrylated linseed oil as a tackifier with ∼50% biomass content, and the peel strength was comparable to commercial tapes and plant-oil-based adhesives. , However, higher biomass content based PSA formulations usually involved petro-sourced monomers during polymerization to enhance the adhesion and peel for real time applications. …”
Section: Introductionmentioning
confidence: 84%
“…For example, with BTSA and BTSEE, though pore size distribution patterns are similar to reactions with BTSE, they show 10% and 7% drops in this "post-curing" region of the TGA, which result in a loss of~0.2 cm 3 /g of cumulative pore volume, equivalent to half the BTSE SSA. In addition, materials with BTSEE in both solvents show oxidation peaks at around 375 • C, this indicates that the ethylene π-bonds remain chemically active for further functionalization [54,55].…”
Section: Cross-linkersmentioning
confidence: 98%